Clinical Parameters and Crestal Bone Loss in Internal Versus External Hex Implants at One Year after Loading - HamidReza Arab; Amir Moeintaghavi; Naser Sargolzaei; MajidReza Mokhtari; Mohammad Derhami; Sepideh Arab; Javad Moosavi (Mashhad University of Medical Sciences, 2015)
Introduction: The survival of an implant system is affected by the choice of antirotational design, which can include an external or internal hex. Implant success also is affected by the maintenance of the crestal bone around implants. The aim of present study was to evaluate the crestal bone loss and clinical parameters related to bone loss in patients loaded with an external or internal hex 3i implant (3i Implant Innovation, Palm Beach Gardens, FL, USA). The evaluations were performed one year after loading. Materials and Methods: A total of 39 implants (23 external hex, 16 internal hex) were placed randomly in 23 patients (10 male, 13 female) by a submerged approach. None of patients had compromised conditions or parafunctional habits. At placement and at one year after loading, periapical radiographs were taken via the parallel method from the implant sites. Results: Crestal bone loss was -0.712±0.831 mm in implants with an internal hex connection and -0.139±0.505 mm in implants with an external hex connection (P≤0.05). No correlation was found between crestal bone loss and parameters such as age, gender, jaw, implant location (anterior, premolar, or molar), implant diameter, or implant length. Conclusions: Crestal bone loss was greater in patients with internal hex 3i implants than in those with external implants. Similar results in other clinical factors were found between the groups.